Dramaturgi som krumtap: En skitse til samarbejder mellem dramaturgiforskning og omverden - Krøgholt, Ida (Peripeti, 2020)
The article suggests how a particular dramaturgical approach to participatory research as accompanying research can be framed. In continuation of a case from Aarhus Theatre, I ask some methodological questions for the concept of participatory and accompanying research, discuss the negotiation of the participatory agenda and come up with a frame for dramaturgical participatory research. The article builds upon the exploration of accompanying research in an earlier article, and it draws on theory of evaluation, action research, participatory research and partnerships, as well as theory of the role of the dramaturge in new dramaturgy.